The effects of transcutaneous neuromuscular electrical stimulation on the activation of deep lumbar stabilizing muscles of patients with lumbar degenerative kyphosis - Kim, So Yeon; Ahn, Sang Ho; Baek, Seung Ok; Kim, Jin Hyun; Jung, Gil Su; Jones, Rodney (Journal of Physical Therapy Science, 2016)
[Purpose] To investigate the effectiveness of three different neuromuscular electrical stimulation (NMES) protocols for the deep lumbar stabilizing muscles of patients with lumbar degenerative kyphosis (LDK). [Subjects and Methods] Twenty patients with LDK were recruited. Three stimulation protocols were investigated: stimulation of the abdominal muscles (protocol A); stimulation of the lumbar muscles (protocol B); and simultaneous stimulation of the abdominal and lumbar muscles (protocol A+B). Images of the obliquus externus (OE), obliquus internus (OI), transversus abdominis (TrA), and lumbar multifidus (LM) muscles were captured by real-time ultrasound imaging (RUSI). [Results] The thickness of LM was significantly greater during stimulation than at rest for all three protocols. Thicknesses of the abdominal muscles (TrA, OI, and OE) were significantly greater during stimulation than at rest for protocols A and A+B. Thickness increases in LM were significantly greater during protocols B and A+B, but not during protocol A. Thickness increases in the abdominal muscles (TrA, OI, and OE) were significantly greater during protocols A and A+B, but not during protocol B. [Conclusion] NMES can significantly activate the deep lumbar stabilizing muscles of patients with LDK. Protocol A+B of NMES is recommended to aid postural correction and low back pain (LBP) in patients with LDK.